Financial feasibility of developing solar groundwater irrigation in Ghana - Xie, Hua; Ringler, Claudia (International Food Policy Research Institute, 2023)
Ghana is home to 32 million people, 13 million of whom live in rural areas and work mostly in agriculture. Although substantial progress has been made, food insecurity still affects a large share of the population; during 2019–2021 more than one third of the population experienced moderate or severe food insecurity, and in 2020 14% of children below the age of five were stunted.